The effects of Shilajit supplementation on fatigue-induced decreases in muscular strength and serum hydroxyproline levels - Joshua L. Keller; Terry J. Housh; Ethan C. Hill; Cory M. Smith; Richard J. Schmidt; Glen O. Johnson (Taylor & Francis Group, 2019)
Background Shilajit is a safe, fluvic mineral complex exudate that is common to Ayurvedic medicine and is composed of fulvic acids, dibenzo-α-pyrones, proteins, and minerals. The purpose of this study was to examine the effects of 8 weeks of Shilajit supplementation at 250 mg·d− 1 (low dose) and 500 mg·d− 1 (high dose) versus placebo on maximal voluntary isometric contraction (MVIC) strength, concentric peak torque, fatigue-induced percent decline in strength, and serum hydroxyproline (HYP). Methods Sixty-three recreationally-active men ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ \overline{X} $$\end{document} ± SD: 21.2 ± 2.4 yr.; 179.8 ± 6.3 cm; 83.1 ± 12.7 kg) volunteered to participate in this study. The subjects were randomly assigned to the high dose, low dose, or placebo group (each group: n = 21). During pre-supplementation testing, the subjects performed 2 pretest MVICs, 2 sets of 50 maximal, bilateral, concentric isokinetic leg extensions at 180°·s− 1 separated by 2-min of rest, and 2 posttest MVICs. Following 8 weeks of supplementation, the subjects repeated the pre-supplementation testing procedures. In addition, the groups were dichotomized at the 50th percentile based on pre-supplementation MVIC and baseline HYP. Mixed model ANOVAs and ANCOVAs were used to statistically analyze the dependent variables for the total groups (n = 21 per group) as well as dichotomized groups. Results For the upper 50th percentile group, the post-supplementation adjusted mean percent decline in MVIC was significantly less for the high dose group (8.9 ± 2.3%) than the low dose (17.0 ± 2.4%; p = 0.022) and placebo (16.0 ± 2.4%; p = 0.044) groups. There was no significant (p = 0.774) difference, however, between the low dose and placebo groups. In addition, for the upper 50th percentile group, the adjusted mean post-supplementation baseline HYP for the high dose group (1.5 ± 0.3 μg·mL− 1) was significantly less than both the low dose (2.4 ± 0.3 μg·mL− 1; p = 0.034) and placebo (2.4 ± 0.3 μg·mL− 1, p = 0.024) groups. Conclusions The results of the present study demonstrated that 8 weeks of PrimaVie® Shilajit supplementation at 500 mg·d− 1 promoted the retention of maximal muscular strength following the fatiguing protocol and decreased baseline HYP. Thus, PrimaVie® Shilajit supplementation at 500 mg·d− 1 elicited favorable muscle and connective tissue adaptations.